Níveis de sobrecarga, ansiedade e depressão de cuidadores de pacientes com doença de Alzheimer participantes e não participantes de grupos de apoio - Artioli, Tábata Brolezzi [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Currently , as a result of the significant increase in the number of elderly, one can observe an increase in the number of chronic diseases , among them Alzheimer's disease (AD) , which affects both patients and their caregivers , that due care with the patient , just overwhelmed , anxious and depressed. Therefore, this study aims to draw a profile of caregivers of Alzheimer's patients, correlating the physical activity of patients with levels of overload, anxiety, depression caregivers. For both sample consisted of 40 patients with AD to characterize the physical activity levels and perform activities of daily living. In addition, we evaluated 40 caregivers. Patient assessment was made through a medical history, beyond the score Clinical Dementia Rating (CDR), Mini - Mental State Examination (MMSE), Modified Baecke Questionnaire for Older Adults (MBQ) , Functional Activities Questionnaire PFEFFER (QAFP) , and the Self Perception Performance in Activities of Daily Living (EAPAVD). For assessing the caregiver was also used an interview, then the Neuropsychiatric Inventory (NPI), anxiety and depression scale (HAD) Scale and the Zarit caregiver burden (Zarit). The data were processed using descriptive procedures for the analysis of characterization of samples, such as cognitive screening and physical activity level and profile of caregivers. There was a normal distribution of the data using the Shapiro Wilk, For data with normal distribution were used parametric descriptive procedures using One Way ANOVA to compare groups and applying a post hoc Bonferroni. As for the data that showed the destruction not normal was used to standardize the test by Z -score , and then treated by means of parametric statistical procedures , as presented earlier . The Pearson correlation was used to identify possible associations between variables. It was assumed significance level of 5 % (p ≤ 0.05) for all analyzes. Given these results, we conclude that...

Atualmente, como consequência da expressiva elevação do número de idosos, pode-se observar um aumento na quantidade de doenças crônico-degenerativas, entre elas, a Doença de Alzheimer (DA), afetando tanto pacientes e seus respectivos cuidadores, que devido aos cuidados com o paciente, acabam sobrecarregados, ansiosos e depressivos. Por isso, esse estudo tem por finalidade traçar um perfil dos cuidadores de pacientes com Alzheimer, correlacionando a prática de atividade física de pacientes com níveis de sobrecarga, ansiedade, depressão de cuidadores. Para tanto a amostra foi constituída por 48 pacientes com DA para caracterização dos níveis de atividade física e realização das atividades de vida diária e seus respectivos cuidadores. A avaliação do paciente foi feita através de uma anamnese, além do Escore de Avaliação Clínica de Demência (CDR), Mini-Exame do Estado Mental (MEEM), Questionário Baecke Modificado para Idosos (QBMI), Questionário de Atividades Funcionais de PFEFFER (QAFP), e a Escala de Auto Percepção do Desempenho em Atividades de Vida Diária (EAPAVD). Para a avaliação do cuidador foi utilizada também uma anamnese, seguida do Inventário Neuropsiquiátrico (NPI), Escala de ansiedade e depressão (HAD) e a Escala de sobrecarga do cuidador de Zarit (Zarit). Os dados foram tratados por meio de procedimentos descritivos para as análises de caracterização de amostras, como rastreio cognitivo e nível de atividade física e perfil de cuidadores. Verificou-se a distribuição da normalidade dos dados por meio do teste de Shapiro Wilk. Para os dados que apresentaram distribuição normal foram utilizados procedimentos descritivos paramétricos utilizando-se o teste Anova One Way para comparação dos grupos e aplicado um Post hoc de Bonferroni. Já para os dados que apresentaram destruição não normal, foi utilizada a padronização por meio o teste Z-score, sendo então tratados por meio de...
Keywords: Educação fisica; Alzheimer, Doença de; Cuidadores; Depressão mental; Ansiedade; Envelhecimento; Anamnese